THE ROLE OF MODERN ACCOUNTING PRACTICES IN DRIVING ECONOMIC GROWTH IN INDIA - Kumari, Puja; Anupam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The aim of this study is to understand how modern accounting practices help drive economic development in India, through its consideration of four sectors identified as critical, namely, Manufacturing, Services, Agriculture, and Trade & Retail, and the contributions were visible through financial performance and broader economic indicators. By using a descriptive research approach and a sample of 200 finance professionals, accountants and business owners, Findings showed a positive association among the use of modern accounting predominately through user-product interfaces such as ERP systems, cloud systems, automated bookkeeping and accounting, and the amount of % contribution to GDP by each sector, as well as tax compliance, and the ability to attract various types of financial flows i.e., equity, treasury, or private investments. The sectoral use of modern accounting and the level of contribution to the economy, showed us that the Services sector records the highest adoption of accounting (88%) has the highest total contribution to the economy (48%), even though MSMEs and startups that adopted modern accounting methodologies reported improvements in their ability to file taxes in a timely manner and be audit-ready, obtain credit and equity and secure short and long-term investment. They stated that their adoption of modern accounting practices improved their reporting capabilities and decision-making confidence. Stakeholder perspectives were also consistent with the results focused on improving accounting and legal transparency, improved decision-making and rebuilding investor confidence. Therefore, the transferable findings presented in this research have suggested that modern accounting practices are not just simply technical updates and upgrades but potentially, a strategic enabler of sustained and inclusive economic development in India.